The Role of the Three Phase Bone Scintigraphy in the Management of the Patients with Costochondral Pain - Koc, Zehra Pinar; Balci, Tansel Ansal; Ozyurtkan, M. Oguzhan (Galenos Yayincilik, 2013)
Aim: The bone scintigraphy is indicated in patients with costochondral pain in order to identify the organic etiology. We aimed to investigate the local and projecting pain, or incidental findings in the three phase bone scintigraphy of the patients referred for costochondral pain. Methods: We included 50 patients (36F, 24M; mean: 41 +/- 18 years-old) referred to our department for three phase bone scintigraphy for costochondral pain between January 2009-July 2012. Results: Among the 50 patients 22 had normal scintigraphy. An increased activity accumulation in the sternoclavicular joint was observed in 12 patients (right in 4, left in 4 and bilateral in 4) only in late phase and in 9 patients (right in 2, left in 1 and bilateral in 6) with increased vascularity. Among projecting pain causes, activity was present on sternum in 4 patients, on humerus in 2 patients and on the first costae in 2 patients. For the characterization of inflammatory pathology, the three phase bone scintigraphy showed sensitivity, specificity, accuracy, positive and negative predictive values of 43%, 94%, 78%, 77% and 78% respectively. Conclusion: Bone scintigraphy is an effective diagnostic method for the identification of local or projecting pain, and additionally unexpected incidental pathologies associated with costochondral pain. However regarding the characterization of inflammatory process false negatives should be considered.
Keywords: scintigraphy; inflammation; musculoskeletal pain